Spatial, functional and temporal Analysis of Wi-Fi hotspots during covid-19 curfew: In selected EU cities Rome, Thessaloniki, Nicosia, Kaunas. - Ivaškevičius, Marius (GEOmedia, 2023)
Behavior of people in extreme condition is one of the main target of the eUMaP project, funded under European Union’s Horizon 2020 project Marie Slodowska-Curie Actions.